(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article analyzes the Illustrated Lecture on a Reimagination of the Ballet Tango (1955), which, through practice-as-research and movement historiography methodologies, examines the work of choreographer Roberto Giachero. The text explores the possibilities of reenactment in the Argentine context as a critical tool for accessing history and piecing together traces of the past. It argues that historical reimagination is a tactic from the Global South for inhabiting the gaps in fragmentary archives and rendering dance present. It concludes that the body is a mediator of knowledge that, through embodied imagination, links the remnants of the archive to the here and now.